2007
DOI: 10.1007/s11418-007-0208-x
|View full text |Cite
|
Sign up to set email alerts
|

Anti-allergic effect of a combination of Citrus unshiu unripe fruits extract and prednisolone on picryl chloride-induced contact dermatitis in mice

Abstract: Effect of 50% ethanolic extract of unripe fruits of Citrus unshiu (CU-ext) on type IV allergic reaction was examined by inhibitory activity of ear swelling of picryl chloride-induced contact dermatitis (PC-CD) in mice. Oral administration of CU-ext and subcutaneous administration of prednisolone showed inhibition of ear swelling during both induction and effector phases of PC-CD. The inhibitory activities of combinations of CU-ext (p.o.) and prednisolone (s.c.) during induction phase of PC-CD were more potent … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
1

Year Published

2009
2009
2013
2013

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 3 publications
0
9
1
Order By: Relevance
“…The combination of CH-ext and prednisolone as well as the combination of various kinds of flavanone glycoside alone and prednisolone exerted synergistic effect without enhancement of adverse reaction of steroidal agents as in the case of the combination of CU-ext and prednisolone as well as the combination of hesperidin and prednisolone [5]. The synergistic effect of combinations of Citrus fruit extract and its flavanone glycosides in combination with prednisolone on ear swelling in PC-CD in mice is a tractable phenomenon.…”
Section: Effects Of Ch-ext Naringin Neohesperidin and Prednisolone mentioning
confidence: 93%
See 3 more Smart Citations
“…The combination of CH-ext and prednisolone as well as the combination of various kinds of flavanone glycoside alone and prednisolone exerted synergistic effect without enhancement of adverse reaction of steroidal agents as in the case of the combination of CU-ext and prednisolone as well as the combination of hesperidin and prednisolone [5]. The synergistic effect of combinations of Citrus fruit extract and its flavanone glycosides in combination with prednisolone on ear swelling in PC-CD in mice is a tractable phenomenon.…”
Section: Effects Of Ch-ext Naringin Neohesperidin and Prednisolone mentioning
confidence: 93%
“…Prednisolone, a reference drug, was subcutaneously administered as in the experiments with combinations of CU-ext and prednisolone [5]. Activity of test samples was evaluated by the increase of ear thickness during induction phase of PC-CD in mice.…”
Section: Effects Of Ch-ext Naringin Neohesperidin and Prednisolone mentioning
confidence: 99%
See 2 more Smart Citations
“…It was reported that extract of unripe Citrus unshiu inhibits ear swelling during both the effector and induction phases in picryl chloride-induced dermatitis model mice. [12] It was also demonstrated that extract of unripe Citrus hassaku and its flavanone glycosides, naringin, and neohesperidin showed antiallergic properties in type I and type IV allergy models in mice. [13] These results suggest that citrus plant extract is beneficial for treatment of allergic dermatitis, but little is known about antiallergic activities of natsumikan.…”
Section: Introductionmentioning
confidence: 99%